Ab initio quantum study of nonadiabatic S1-S2 photodynamics of s-trans-butadiene - Komainda, Adrian; Ostojić, Bojana; Köppel, Horst (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2013)
The nonadiabatic photodynamics of s-trans-butadiene in its lowest singlet excited states is studied theoretically, using a fully quantal approach. The coupled 1Bu and 2Ag states are considered in the calculation, representing the lowest dipole-allowed electronic transition, and the dipole-forbidden state with substantial double-excitation character, respectively. Up to six nuclear degrees of freedom, including out-of-plane dihedral angles, are included. The calculation of the underlying potential energy surfaces relies on the CASPT2 method, where widely different CAS spaces have been compared. The ultrafast electronic population decay is confirmed, proceeding on a time scale of 30-40 fs. Pronounced out-of-plane distortions are obtained for the first time from fully quantal calculations. The complexity of the electronic absorption spectrum increases substantially upon including additional vibrational modes in the calculation. Further computations were performed to facilitate inclusion of the coupling to the ground state in subsequent work.
Im Titel sind die Zahlen 1 und 2 bei S tiefgestellt
Gesehen am 01.12.2021